Analysis on Performance of Screw Compressor in MVR system. (August 2019) - Liu, Guangbin; Zhao, Xiaoyan; Liansheng, Li; Bin, Tang; Qichao, Yang; Yuanyang, Zhao
Abstract: Screw compressor is suitable for small scale mechanical vapor recompression (MVR) system especially for the solution with high boiling point elevation. In this paper, a mathematical model of screw compressor in MVR system is built and its working process is simulated. The results show that water injection improves the efficiency of screw compressor obviously and the compression process along saturated vapor line is realized if enough water is injected. The volumetric and isentropic efficiency is not sensitive with the water if more than flow rate of 35L/h is injected. The discharge temperature decreases from 133.4°C to 108°C with water quantities of 5L/h to 35L/h and then it is constant . The large saturated heat transfer difference in evaporator leads to decrement of volumetric efficiency but increment of isentropic efficiency. The mass flow rate of distilled water increase from 0.38t/h to 2.56 t/h and the saturated temperature difference increases from 4°C to 26.9°C when the rotating speed increases from 1000 rpm to 6000rpm.